EFISIENSI PERBANKAN DI INDONESIA DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) SEBAGAI PERTIMBANGAN KINERJA PERBANKAN - Ridho Muarief; Miranti Miranti (POLITEKNIK LP3I JAKARTA, 2022)
To implement sound banking principles, the assessment of bank efficiency is very important. This is because efficiency is a picture of a bank's performance as well as a factor that must be considered by the bank to act rationally in minimizing the level of risk faced in dealing with its operational activities. This study aims to measure the relative efficiency of banks in Indonesia using the Data Envelopment Analysis (DEA) methodology based on the intermediation approach. The research samples are Mandiri, BRI, BNI, BCA, and BTN. DEA is a methodology with a non-parametric-deterministic approach that aims to determine the relative efficiency and managerial performance, based on empirical data by determining the input and output of a UPK (Decision Making Unit). The results showed that BNI was relatively inefficient during the study years. Bank Mandiri was efficient in 2013. BCA was relatively inefficient during the study years. BRI experienced perfect efficiency level in 2013. BTN experienced perfect efficiency level from year to year. Overall, the commercial banks that are widely referenced by other commercial banks are BRI in 2011, BTN, BNI, and Bank Mandiri in 2013. The summary of potential improvement shows that the combined sources of inefficiency in banks are revenue needs to be increased by 35.58% and credit needs to be increased by 31.83%. While deposits need to be reduced by 9.49%, total assets need to be reduced by 1.51%, and interest expenses reduced by 21.48%.Key words: Banking, Efficiency, DEA Methodology Approach.